2011
DOI: 10.2478/v10042-010-0096-x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study in osteoinduction by a nano-crystalline hydroxyapatite in the mini pig.

Abstract: Abstract:To test the probable osteoinductive properties of NanoBone®, a new highly non-sintered porous nano-crystalline hydroxylapatite bone substitute embedded into a silica gel matrix, granules were implanted subcutaneously and intramuscularly into the back region of 18 mini pigs. After periods of 5 and 10 weeks as well as 4 and 8 months, implantation sites were investigated using histological and histomorphometric procedures. Signs of early osteogenesis could already be detected after 5 weeks. The later per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Despite the presence of micro- and nanopores, NB in its granular form within caprine muscle probably did not induce sufficient mineral ion influx and protein-related surface modifications, which are suggested as a requirement to trigger osteoinduction [27-29]. On the other hand, another in vivo study in mini pigs reported a marked osteoinduction within subcutaneous as well as muscle implantation sites induced by the very same NB-granules [12]. Thus, we assume that the lack of osteoinductivity of NB in the present study could be explained on the basis of its application form, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the presence of micro- and nanopores, NB in its granular form within caprine muscle probably did not induce sufficient mineral ion influx and protein-related surface modifications, which are suggested as a requirement to trigger osteoinduction [27-29]. On the other hand, another in vivo study in mini pigs reported a marked osteoinduction within subcutaneous as well as muscle implantation sites induced by the very same NB-granules [12]. Thus, we assume that the lack of osteoinductivity of NB in the present study could be explained on the basis of its application form, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with bone marrow stromal cells [31], however, and along with hydroxyapatite as biphasic calcium phosphate ceramics [32-34], it has been shown to induce different degrees of osteoinductivity, even in ectopic tissues. With regard to objectivity, it has to be considered whether the used ß-TCP granules would have shown some osteoinductive properties, when implanted into the subcutaneous or muscle tissue of the mini-pig as was done for NB [12]. Furthermore, it has to be emphasized that for ß-TCP, osteoinduction has been demonstrated in dogs [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TCP and HAp are both chemically similar to the inorganic component of bone and are osteoconductive because of their capability to bond with bone. TCP lacks osteoinductivity, while HAp is widely accepted to be osteoinductive [7, 8]. On the other hand, HAp degrades over the course of several years, whereas TCP may be resorbed into the new bone tissue [9, 10].…”
Section: Introductionmentioning
confidence: 99%